Analisis Penerapan Strategi Pemasaran dalam Meningkatkan Pengguna Aplikasi Ageu Jek di Kabupaten Purwakarta - Amalia, Dinda; Puspasari, Dewi; Fitriani, Dini; Hendraliany, Srie (Jurnal EMT KITA, 2024)
Competition in the online transportation industry is getting tighter, with the presence of various platforms such as Go-Jek, Grab, and Ageu Jek. Ageu Jek, a local platform in Purwakarta Regency, faces challenges to increase its app users. This study aims to analyze Ageu Jek's marketing strategy implementation in increasing app users in Purwakarta Regency. This research uses qualitative methods with interview and observation techniques. The research informants are Ageu Jek application owners, Ageu Jek drivers, and Ageu Jek application users. The results showed that Ageu Jek faces several challenges, such as the lack of public awareness about the app, fierce competition with other platforms, and incomplete app features. Ageu Jek's marketing strategy still needs to be optimized, focusing on promotion through social media, developing app features, and improving service quality. Ageu Jek needs to improve its marketing strategy by focusing on market analysis, market segmentation and the right target audience. Application feature development and service quality improvement also need to be considered. With the right strategy, Ageu Jek can increase its application users and become a competitive online transportation platform in Purwakarta Regency.